Pandemic diseases preparedness and response in the age of COVID‐19—a symposium report. Issue 1 (5th November 2020) - Cable, Jennifer; Heymann, David L.; Uzicanin, Amra; Tomori, Oyewale; Marinissen, Maria Julia; Katz, Rebecca; Kerr, Larry; Lurie, Nicole; Parker, Gerald W.; Madad, Syra; Maldin Morgenthau, Beth; Osterholm, Michael T.; et al.
Abstract: For years, experts have warned that a global pandemic was only a matter of time. Indeed, over the past two decades, several outbreaks and pandemics, from SARS to Ebola, have tested our ability to respond to a disease threat and provided the opportunity to refine our preparedness systems. However, when a novel coronavirus with human‐to‐human transmissibility emerged in China in 2019, many of these systems were found lacking. From international disputes over data and resources to individual disagreements over the effectiveness of facemasks, the COVID‐19 pandemic has revealed several vulnerabilities. As of early November 2020, the WHO has confirmed over 46 million cases and 1.2 million deaths worldwide. While the world will likely be reeling from the effects of COVID‐19 for months, and perhaps years, to come, one key question must be asked, How can we do better next time? This report summarizes views of experts from around the world on how lessons from past pandemics have shaped our current disease preparedness and response efforts, and how the COVID‐19 pandemic may offer an opportunity to reinvent public health and healthcare systems to be more robust the next time a major challenge appears.